PENGARUH PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP KARAKTER RELIGIUS DAN DISIPLIN SISWA KELAS V DI SDN GUNUNG PUTRI 04 - Sarah Awaliya; Muhyani; Andestend (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the effect of using the Think Pair Share (TPS) cooperative learning model on the formation of religious character and discipline in fifth-grade students at SDN Gunungputri 04. The background of this study stems from the urgency of strengthening students' character, particularly in terms of religiosity and discipline, through learning methods that encourage active student involvement. This study uses a quantitative approach with a quasi-experimental design. The research subjects consist of two groups: an experimental class that received the TPS learning model treatment and a control class that followed conventional learning. Data were collected using questionnaires and observation sheets to evaluate students' religious character and discipline. The analysis results showed significant differences between the two groups. Students who learned using the TPS approach demonstrated better improvements in religious character and discipline compared to students in the control group. Based on these findings, it can be concluded that the Think Pair Share model has a positive impact on the development of students' religious character and discipline. Therefore, this model is recommended as one of the learning approaches worthy of implementation in character education at the elementary school level.